Identifikasi Bakteri Patogen Pascapanen Jagung Pakan (Zea mays L.) - Maulana, Ahmad; Marsuni, Yusriadi; Budi, Ismed Setya (www.ulm.ac.id, 2025)
Postharvest plant pest organisms include bacteria. This research aims to determine the colony morphology characteristics and physiology of post-harvest pathogenic bacteria of feed corn (Zea mays L.), and to determine its genus. The method used was purposive sampling and samples were taken from the PT. Arutmin Indonesia Site Satui storage warehouse in Satui District, Tanah Bumbu Regency. Bacteria isolated from samples and positive for being pathogenic on corn seeds were identified by observing the colony's morphological characteristics and physiology. The results showed that the pathogenic bacteria identified were bacteria from the genus Dickeya and there were still bacteria of unknown genus, and no bacteria from the genus Pantoea were found. The first bacteria of the Dickeya genus are white with a grayish circular pattern in the middle, round to irregular shape, uneven edges, flat surface, and not shiny. These characteristics are the same as those of the Dickeya zeae bacteria. The second Dickeya genus of bacteria looks grayish white in the middle and bright white at the edges, round to irregular in shape, the edges look slightly blurry and slightly stringy, the surface is convex to flat, and shiny. These characteristics are the same as those of the Dickeya chrysanthemi bacteria. Based on their physiological characteristics, the bacteria obtained have similarities with the bacteria of the genus Dickeya, namely they are gram negative, can grow in aerobic and anaerobic conditions, can produce the catalase enzyme, are not yellow if grown on YDC media, can cause soft rot, and can produce the enzyme lecithinase.